2020
DOI: 10.1128/aac.02183-19
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Gram-Negative Bacterial Infections in Children

Abstract: Carbapenem-resistant organisms (CRO) are a major global public health threat. Enterobacterales hydrolyze almost all β-lactams through carbapenemase production. Infections caused by CRO are challenging to treat due to the limited number of antimicrobial options. This leads to significant morbidity and mortality. Over the last few years, several new antibiotics effective against CRO have been approved. Some of them (e.g., plazomicin or imipenem-cilastatin-relebactam) are currently approved for use only by adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 142 publications
0
48
0
Order By: Relevance
“…In studies elsewhere, patients with comorbidities, ICU stay, immunosuppression, the two extremities of age, and exposure to multiple antibiotics before the initial culture considered as risk factors for acquiring CR. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…In studies elsewhere, patients with comorbidities, ICU stay, immunosuppression, the two extremities of age, and exposure to multiple antibiotics before the initial culture considered as risk factors for acquiring CR. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical infections caused by AMR bacteria, especially carbapenem-resistant Enterobacteriaceae (CRE) and Acinetobacter spp. (CRA), largely limit the effective prevention and treatment strategies resulting in a high mortality [2,3]. Tigecycline, the minocycline derivative 9-tert-butyl-glycylamido-minocycline, is the third generation of tetracycline family antibiotic which negates most tetracyclines resistance mechanisms due to ribosomal protection and drug efflux [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the continual use of carbapenems and polymyxins to treat bacterial infections resistant to penicillins, cephalosporins, and carbapenems are increasing the rate of resistance to these last-resort antibiotics 2,4,9,11 . The emergence of carbapenem-and/or polymyxin-resistant MDR infections is thus limiting therapeutic options and increasing hospital stay, healthcare costs, morbidity, and mortality [12][13][14] . Subsequently, the WHO has classified carbapenem-resistant Gram-negative bacteria (CR-GNB) as critical priority pathogens for which novel antibiotics are urgently needed 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of the literature showed the absence of a review addressing carbapenem and polymyxin resistance among pregnant women and neonates. Only one review addressed carbapenem-resistance among Gram-negative bacteria (GNB) in children 14 whilst another only addressed CRE-causing neonatal sepsis in China 38 . Thus, this is the first work to systematically review and statistically analyse the literature on carbapenem and polymyxin resistance among pregnant women and infants.…”
Section: Introductionmentioning
confidence: 99%